Validação de genes diferencialmente regulados em modelo animal de crises epilépticas audiogênicas - Samara Damasceno (2015)
The Wistar Audiogenic Rat (WAR) is an animal model of audiogenic seizures developed from the selection of sensitive Wistar to sound stimulus. Because of the similarities with epileptic events in humans, this model is highly relevant, and it may contribute to the knowledge of generalized tonic-clonic seizures, complex partial seizures and reflex seizures. Nevertheless, little is known about the molecular genetic aspects related to the susceptibility of this strain to seizures. The aim of this research was to confirm differentially regulated genes in two neural substrates in WAR animals, study these genes and identify relevant biological pathways in the model in order to contribute to the understanding of the epileptic condition. For this, the following structures were used: quadrigeminal plate and hippocampus of WAR and Wistar submitted to sound stimulation. Validations were done using real time quantitative PCR and identification of pathways by programs DAVID/KEGG. Genes Gabbr1, Gria2, Grin1, Scn2a1 and Il18 in quadrigeminal plate and genes Gabra2, Gabbr1, Gria2 and Slc1a3 in the hippocampus of WAR animals were confirmed as differentially transcribed when compared to controls Wistar. Two of the selected genes did not show regulation with a significant difference but showed a trend. Some of these genes are involved in glutamatergic and GABAergic neurotransmission pathways, both discussed in models of epilepsy e here identified as relevant in quadrigeminal plate and in the hippocampus of audiogenic rats. The downregulation of the GABA receptor genes stood out in the hippocampus of WARs suggesting that the GABAergic system is critical to that structure. Calcium signaling pathway was also identified as relevant in the epileptic condition but significant only for quadrigeminal plate. By different mechanisms, this pathway can mediate neuronal hyperexcitability and thus promote the emergence of seizures. Our results show that genes related to ion channels are modulated in quadrigeminal plate and in the hippocampus of WARs submitted to acoustic stimulation and suggests the calcium signaling pathway as another field of study for understanding the epileptic condition in Wistar Audiogenic Rat model.